One Hundred Years of Turkish Foreign Policy (1923-2023)
XXVII, 254 p.
Keywords: This book brings together an all-women group of scholars to provide a historically grounded and theoretically rich examination of the continuities and changes in Turkey’s foreign policy since the Republic's establishment in 1923. Using different International Relations theories, clarifying the interaction between domestic politics and foreign policymaking, the book charts the evolution of Turkey’s foreign policy vis-a-vis several regions and global actors and examines the major developments in Turkey’s relations with these actors. Some chapters emphasize the continuities in Turkey’s external relations, and others examine the significant changes and discontinuities in certain areas. Recognizing that Turkey’s state interests may not always coincide with the interests of the ruling elite, the book demonstrates that the centennial birthday of Turkey represents a constitutive moment for Turkey’s future and calls for a pragmatic, as opposed to a completelyideologically-based, grand strategy that should focus on progressive ideals.